EVALUATION OF THE KNOWLEDGE OF NURSES WORKING IN THE OBSTETRICS AREA ON SHOULDER DYSTOCIA (CIPEEX, 2025)
Shoulder dystocia is an obstetric emergency and can bring serious complications for both the mother and the newborn, and it is extremely important that the doctor and their team are prepared to recognize and treat this situation in the best possible way. Therefore, the objective of the study was defined as evaluating the knowledge of nurses working in the obstetrics area on the conduct and management of shoulder dystocia. This work is a cross-sectional, descriptive, and quantitative study, conducted in maternity hospitals and hospitals in the cities of Anápolis and Goiânia-Goiás. Data were collected through an authorial questionnaire applied to obstetric nurses. For analysis, Pearson's chi-square and Fisher's exact test were used. Of the 29 participants, 93.1% had undergone practical training. Only 9 had taken the Advanced Life Support in Obstetrics course, but 68.96% of the total participants had satisfactory knowledge of the ALEERTA mnemonic. The most applied maneuvers were McRoberts and Rubin I, with an average resolution time for shoulder dystocia of 2.31 minutes. Comparing nurses who took the course and those who did not, *p*=1.000 was observed in the comparison of the confidence level in managing shoulder dystocia between the subgroups and *p*>0.05 in the percentage of correct answers for all 3 parts of the questionnaire. It is concluded that, in the present sample, no significant difference (*p*
Keywords: Shoulder Dystocia; Health Professionals; Simulation Training